Magic, Genderfluidity, and queer Vikings, ca. 750‐1050. Issue 5 (27th April 2021) - Bell, Jacob
Abstract: From the Nazi Reich to the deadly storming of the U.S. Capital building on January 6, 2021, symbols of pre‐Christian Norse religious practices, especially magic, have come to represent androcentricity, authoritarianism, and White nationalism. This modern misrepresentation contrasts how the Norse people themselves potentially saw these same signs and images: as subversive, subaltern, and queer. Rather than the austere and distorted image left to us by monastic chroniclers of later centuries, recent historical, archaeological, and literary studies have taken into consideration new evidence that suggests magic was a vibrant and interwoven part of everyday life for the Norse people in the Viking Age. New methodological approaches and material discoveries have enabled scholars to re‐evaluate the socio‐sexual systems of Viking‐Age Scandinavia and theorize about the potential for ungendered, transgendered, and gender‐fluid readings of how individuals subverted these regimes through sorcery. This article surveys this recent turn in Old Norse studies and explores the possibilities for such scholarship to revolutionize how we think of the Vikings' place in the circum‐polar history of Shamanism, gender‐bending, and queer magic.